Capturing and Quantifying Particle Transcytosis with Microphysiological Intestine‐on‐Chip Models. Issue 1 (22nd December 2022) - Delon, Ludivine C.; Faria, Matthew; Jia, Zhengyang; Johnston, Stuart; Gibson, Rachel; Prestidge, Clive A.; Thierry, Benjamin
Abstract: Understanding the intestinal transport of particles is critical in several fields ranging from optimizing drug delivery systems to capturing health risks from the increased presence of nano‐ and micro‐sized particles in human environment. While Caco‐2 cell monolayers grown on permeable supports are the traditional in vitro model used to probe intestinal absorption of dissolved molecules, they fail to recapitulate the transcytotic activity of polarized enterocytes. Here, an intestine‐on‐chip model is combined with in silico modeling to demonstrate that the rate of particle transcytosis is ≈350× higher across Caco‐2 cell monolayers exposed to fluid shear stress compared to Caco‐2 cells in standard "static" configuration. This relates to profound phenotypical alterations and highly polarized state of cells grown under mechanical stimulation and it is shown that transcytosis in the microphysiological model is energy‐dependent and involves both clathrin and macropinocytosis mediated endocytic pathways. Finally, it is demonstrated that the increased rate of transcytosis through cells exposed to flow is explained by a higher rate of internal particle transport (i.e., vesicular cellular trafficking and basolateral exocytosis), rather than a change in apical uptake (i.e., binding and endocytosis). Taken together, the findings have important implications for addressing research questions concerning intestinal transport of engineered and environmental particles. Abstract : Intestine‐on‐chip model study with in silico modeling demonstrates that the rate of nanoparticle transcytosis is ≈350x higher across Caco‐2 cell monolayers cultured under fluid shear stress compared to "static" configuration in Transwell. This drastically enhanced and energy dependent nanoparticle transport is independent of apical uptake and recapitulate the in vivo transcytotic activity of enterocytes.